2022
DOI: 10.3390/diagnostics12020410
|View full text |Cite
|
Sign up to set email alerts
|

Performance of WHO-Endorsed Rapid Tests for Detection of Susceptibility to First-Line Drugs in Patients with Pulmonary Tuberculosis in Bangladesh

Abstract: The fast and accurate detection of susceptibility in drugs is a major challenge for a successful tuberculosis (TB) control programme. This study evaluated the performance of WHO-endorsed rapid diagnostic tools, such as BACTEC MGIT 960 SIRE (MGIT SIRE), GenoType MTBDRplus (MTBDRplus) and Xpert MTB/RIF (Xpert), for detecting susceptibility to first-line anti-TB drugs among pulmonary TB patients in Bangladesh. A total of 825 sputum samples with results from drug susceptibility testing (DST) against first-line ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
2
7
0
1
Order By: Relevance
“…Mutations in katG, kasA, inhA, fabG1 genes and the oxyR-ahpC intergenic region are associated with conferring resistance to isoniazid (44,62,63), thus ethA/R mutations are associated with ethionamide resistance (48,64,65). Our results were in concordance with previous studies (44,63,66) due to the higher prevalence of mutations in katG (88.8%). Furthermore, it has been shown that mutations in the ahpC promoter conferred resistance by compensatory mechanism (67,68) like L427P in the katG gene (69,70).…”
Section: Discussionsupporting
confidence: 94%
“…Mutations in katG, kasA, inhA, fabG1 genes and the oxyR-ahpC intergenic region are associated with conferring resistance to isoniazid (44,62,63), thus ethA/R mutations are associated with ethionamide resistance (48,64,65). Our results were in concordance with previous studies (44,63,66) due to the higher prevalence of mutations in katG (88.8%). Furthermore, it has been shown that mutations in the ahpC promoter conferred resistance by compensatory mechanism (67,68) like L427P in the katG gene (69,70).…”
Section: Discussionsupporting
confidence: 94%
“…In the case of the first-line drug in Mtb treatment, mutations in the 81-bp rifampicin resistance determining region (RRDR) of the rpoB gene, also known as a hotspot region, have been accurate predictors of rifampicin resistance in many studies [69][70][71]. On the other hand, it has been established that INH resistance, predominantly mediated through loss of catalase-peroxidase activity via mutations in katG, produces high-level resistant strains [18,72,73]. Finally, in ethambutol, most resistance-related genes are located on the embB, embC, and upstream of the embA [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, due to drug resistance rising worldwide, the WHO proposed expanding rapid testing and detection of cases as one of the five high-priority actions to tackle the global DR-TB crisis [15]. As part of these actions, some molecular biology-based diagnostic methods have been applied in a clinical setting for their versatility and speed, including variants of Xpert MTB/RIF and Geno-Type MTBDRplus [16][17][18][19]. Although these methods are rapid and straightforward, Mtb continuously evolves through the genomic acquisition of single nucleotide polymorphisms (SNPs), insertions, and deletions (indels), impacting the ability to discriminate strains without the classic regions used for resistance detection [20].…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis (TB) disease is a chronic infectious disease caused by Mycobacterium tuberculosis (MTB). Globally, there were an estimated 9.9 million new cases of MTB in 2020 [1], and about half a million of these cases were multidrug-resistant TB (MDR-TB) [2]. The emergency of drug-resistant TB (DR-TB) has threatened global public health efforts to control TB [3,4].…”
Section: Introductionmentioning
confidence: 99%